Study Of A Far Infrared Cavity At The Galactic Plane - Gautam, A. K.; Aryal, B. (Scientific World, 2021)
A far infrared dust cavity nearby AGB star namely AGB19+26 found to be located, centered at R.A.(J2000)= 20h 02m 02.8s and Dec.(J2000)= 26° 52' 36.8".Distribution of Planck function, dust color temperature, dust mass and visual extinction of the far infrared cavity was studied. This cavity was found to have following properties: (a) it is located nearby AGB star named AGB19+26around far infrared loopG064-01 at 2000 pc, (b) it is close to the Galactic plane at galactic latitude -1.2° therefore the radiation field is strong and (c) the diameter of the cavity is greater than 0.2° on IRAS. The dust color temperatures are found to be in the range 21.48 ± 0.25 K to 22.03 ± 0.12 K. Planck function was found to be non-uniform along its extension and compression, suggesting that the dust and grains are not in the local thermodynamic equilibrium, possibly because of external cause. It is therefore, a deviation from the Gaussian distribution is noted in the histogram of dust color temperature. It is concluded that the cavity was formed due to the high pressure events occurred in the past.